Resveratrol: from diet to topical usage. Issue 11 (16th October 2017) - Chedea, Veronica Sanda; Vicaş, Simona Ioana; Sticozzi, Claudia; Pessina, Federica; Frosini, Maria; Maioli, Emanuela; Valacchi, Giuseppe
Abstract : Molecular pathways involved in resveratrol mediate skin protective effects against environmental insults. Abstract : The stilbene derivative resveratrol (3, 5, 4′-trihydroxy-stilbene; RESV) has become the subject of interest of many researchers and the pharmaceutical industries due to its well-acclaimed beneficial biological activities. Although earlier research tended to focus on the effects of RESV on cardiovascular disorders, many other studies have described the beneficial effects of RESV in the areas of cancer chemoprevention and inflammation and interest of researchers on this compound is still increasing. It is now well accepted that the effect of RESV is not just due to its so called "antioxidant" activity but mainly (if not only) because of the ability of this compound to trigger cell signaling pathways and gene expression involved in cellular defense systems. Many " in vitro " studies on RESV did not take into account that although its oral absorption is about 75% it undergoes rapid metabolism and the concentration in the blood stream is almost undetectable. For this reason interest in the topical usage of RESV by cosmeceutical skin care brands has exponentially increased in the last decade reporting in general very promising results on its beneficial effect in protecting the skin from outdoor insults, but there is still some controversy on its topical usage mainly surrounding the concentration used. Therefore, more basic research on the topical application of RESV should be performed to better understand the way it prevents cutaneous damage and whether it could be recommended as a preventive skin aging agent for all skin insults.